An adaptive current control scheme for high-performance AC drives - Tsai, MF; Tzou, YY (My University, 1997)
In this paper, a self-tuning adaptive current controller for high-performance sc drives is presented. The adaptive current controller, which operates in the stationary two-axis frame to provide the persistently exciting condition for parameter estimation convergence, consists of an one-step-ahead predictive controller and a model estimator. The predictive controller's parameters are adjusted adaptively on line in terms of estimated model parameters. Estimating the model parameters entails a first-order four-dimensional least-squares estimator with exponential data weighting to detect the variations of the motor parameters and the back emf. The proposed adaptive control scheme is implemented in parallel by IMS T800-20 transputers. Simulation results show the effectiveness of the proposed adaptive current control scheme.